Perbandingan Kualitas Bolu Kukus Mekar Gula Aren dan Gula Kelapa - Serly Riyanti; Cucu Cahyana; Annis Kandriasari (Garina, 2024)
This research aims to identify and analyze the quality comparison between steamed cakes made with palm sugar and those made with coconut sugar. The research employs an experimental method and involves 40 moderately trained panelists as the sample. Based on the quality analysis test results, the highest average scores in all aspects were achieved by the steamed cakes made with palm sugar. Specifically, for the color aspect, a score of 4.6 was in the range of brown to very dark brown categories. The blooming aspect received a score of 4.4, which was in the range of bloomed to very bloomed categories. The volume aspect received a score of 4.45, falling within the large to very large categories. The aroma aspect scored 4.5, ranging from a palm sugar aroma to a very strong palm sugar aroma. The texture aspect scored 4.5, which was in the range of soft to very soft categories. The taste aspect scored 4.4, within the sweet to very sweet categories. Based on the statistical hypothesis test with the Mann-Whitney U test at a significance level of α=0.005, it was found that there is a quality difference between the steamed cakes made with palm sugar and those made with coconut sugar in terms of color and aroma. However, there was no quality difference in the aspects of blooming, volume, texture, and taste